2020
DOI: 10.1021/acs.jpcc.0c09531
|View full text |Cite
|
Sign up to set email alerts
|

The XtalOpt Evolutionary Algorithm for Crystal Structure Prediction

Abstract: Significant progress has been made in the field of a priori crystal structure prediction, with a number of recent remarkable success stories. Herein, we briefly outline the methods that have been developed for finding the global minimum structure and interesting local minima without the need for experimental information. Focus is placed on describing the XtalOpt evolutionary algorithm (EA) developed in our group toward this end. XtalOpt is published under well-known open-source licenses, and the EA searches ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 216 publications
0
50
0
Order By: Relevance
“…Whereas the first three are best suited for local exploration, the latter three can broadly traverse the PES. Quantifying the performance of an algorithm is difficult due to their stochastic nature, however it has been shown that various options can greatly enhance the success rate 64 .…”
Section: Computational Techniques a Computational Methodologiesmentioning
confidence: 99%
“…Whereas the first three are best suited for local exploration, the latter three can broadly traverse the PES. Quantifying the performance of an algorithm is difficult due to their stochastic nature, however it has been shown that various options can greatly enhance the success rate 64 .…”
Section: Computational Techniques a Computational Methodologiesmentioning
confidence: 99%
“…The stoichiometries of the doped phases we considered were S x P 38 In this case the EA searches were seeded with doped supercells from the previously reported Im3m H 3 S and R3m H 3 S structures. 19 The CSP searches were performed using the open-source evolutionary algorithm (EA) XTALOPT [44][45][46] version 12. 47 The initial generation consisted of random symmetric structures that were created by the RANDSPG algorithm, 48 and the minimum interatomic distance between S-S, S-H, S-P, H-H, H-P, and P-P atoms were constrained to 0.88, 0.71, 0.93, 0.53, 0.76 and 0.98 Å using a uniform scaling factor of 0.5 multiplied by tabulated covalent radii.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the past two decades, a plethora of CSP codes have been developed based on evolutionary (or genetic) algorithms (EAs/GAs), including XtalOpt, [53,78,[149][150][151][152][153][154] GASP, [155] USPEX, [55,156,157] MAISE, [56] EVO, [57], and other codes developed by Trimarchi et al, [58,158], Abraham et al, [59] Fadda et al, [60], Woodley and Catlow [159], Hammer et al [160], and the "adaptive-Ga" of Wentzcovitch et al [68]. These codes are coupled with periodic first-principle simulation packages or interatomic potentials for local optimizations.…”
Section: Evolutionary Algorithmsmentioning
confidence: 99%